Toxic Effects of Sodium Dodecyl Sulphate on Grass Carp Ctenopharyngodon idella - Susmi, T S; Rebello, Sharrel; Jisha, M S; Sherief, P M (Fishery Technology, 2025)
Sodium dodecyl sulphate, an anionic detergent finds various applications in household, industrial, laboratory and pharmaceutical preparations.This paper reports the histological, enzymatic and microbial changes found in the gills of Grass Carp (Ctenopharyngodon idella) induced by the acute action of Sodium dodecyl sulfate (SDS). A 96 h LC50 value of 7.7 mg/ l of SDS was obtained using static bioassay method. Sets of twenty grass carps each were exposed to nominal concentrations (2, 2.5 and 3 mg/l) of SDS for 30 days and the changes in the gills were monitored every tenth day. Extensive gill damage with necrosis and intraepithelial oedema was observed. This was accompanied by increased levels of antioxidant enzymes viz., superoxide dismutase and catalase. The gills of SDS treated fishes also showed an increased rate of microbial attack predominantly by Aeromonas sp, Micrococcus sp and Bacillus sp. Extensive necrosis, and increased rate of microbial attack suggested that SDS incites an acute inflammatory response. The morpho-histochemical changes in the gills provoked functional disorders viz., asphyxia and loss of osmotic and ionic regulation that may ultimately play a significant role in the mortality of Grass Carp exposed to SDS.